2021
DOI: 10.1039/d0fo03152f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lotus seedpod oligomeric procyanidins on AGEs formation in simulated gastrointestinal tract and cytotoxicity in Caco-2 cells

Abstract: This study explored the effects of lotus seedpod oligomeric procyanidins (LSOPC) and their main monomer catechin (CC) on the formation of advanced glycation end products (AGEs) and Caco-2 cytotoxicity during gastrointestinal digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…According to the preparation of various traditional medicines; for example, Chinese traditional medicines, Kampo medicines (the traditional Japanese herbal medicines), and Thai traditional medicines, these raw plant materials are commonly used in the form of an extract [ 12 , 13 , 14 , 15 ], following the traditional knowledge that the extract, which consists of major bioactive compounds, will provided synergistic effects for the health benefits of mankind. Nowadays, the number of research studies on the potential pharmacological activities of N. nucifera are considerably increased [ 7 , 8 , 9 , 10 , 11 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the preparation of various traditional medicines; for example, Chinese traditional medicines, Kampo medicines (the traditional Japanese herbal medicines), and Thai traditional medicines, these raw plant materials are commonly used in the form of an extract [ 12 , 13 , 14 , 15 ], following the traditional knowledge that the extract, which consists of major bioactive compounds, will provided synergistic effects for the health benefits of mankind. Nowadays, the number of research studies on the potential pharmacological activities of N. nucifera are considerably increased [ 7 , 8 , 9 , 10 , 11 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals from lotus seedpods have been determined to reveal a variety of biological activities, including ameliorating cognitive impairment ( 10 12 , 52 61 ), antioxidation ( 4 , 5 , 62 64 ), antibacterial ( 15 17 , 65 ), anti-glycative ( 7 , 18 , 19 ), neuroprotection ( 48 , 66 ), anti-tyrosinase ( 46 , 47 ), retinal protection ( 6 ), anti-insomnia ( 67 ), anti-cancer ( 68 ), immunomodulatory ( 69 ), ameliorating intestinal injury ( 70 ), anti-diabetes ( 20 ), regulating lipid homeostasis ( 38 ), anti-inflammatory ( 71 ) and α-glucosidase inhibitory ( 4 ) activities.…”
Section: Biological Activity Of Phytochemicals From Lotus Seedpodsmentioning
confidence: 99%
“…A variety of phytochemicals have been derived and identified from lotus seedpods, including proanthocyanidins ( 6 ), oligomeric procyanidins ( 7 ), polyphenols ( 8 ), flavonoids and others ( 9 ). Numerous studies have demonstrated that extracts and phytochemicals of lotus seedpods possessed various biological activities, such as ameliorating cognitive impairment ( 10 12 ), antioxidation ( 8 , 9 , 13 , 14 ), antibacterial ( 15 17 ), anti-glycative ( 7 , 18 , 19 ) and anti-diabetes ( 20 ). Due to the good biological activities and superior physicochemical property, raw material, extracts and phytochemicals of lotus seedpods have been increasingly applied in food and other industries ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…As this lotus plant is widely used in both foods and herbal medicines, there are a large number of studies on its biological activities [ 8 , 9 , 10 , 11 , 12 , 13 ]. Most of the previous research studies focus on the leaves of N. nucifera ; for example, Lin and his team [ 3 ] isolated flavonoid phytochemical compounds from a leaf extract and reported on their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%